The influence of socio-psychological factors on residents' willingness to practice sustainable waste handling in Dammam City, Saudi Arabia - Ahmed Labib, Ossama; Abd Manaf, Latifah; Sharaai, Amir Hamzah; Mohamad Zaid, Siti Sarah; Khalil, Muhammed Salisu (Multidisciplinary Digital Publishing Institute, 2023)
An increase in solid waste production may affect sustainable solid waste handling practices such as indirect disposal and sanitary landfilling. The objective of this study was to explore the possibility of Dammam residents’ participation in sorting and recycling by comparing sustainable waste handling practices from different income level groups according to family income levels to determine the impacts of independent variables on the willingness of residents to participate in sustainable waste handling practices. There was a statistically significant difference between low and high levels of awareness and perceived behavior control in Dammam City households’ willingness to sort waste and recycle; however, at the middle level, there was only a significant difference in perceived behavior control. Moreover, there was a statistically significant difference between high and middle levels in government facilitators regarding sorting and recycling willingness in Dammam City. The descriptive analysis comprised 450 participants (37.8) in middle levels, (44.2), high levels, and (18) low levels. The results of the participants’ attitudes consisted of sorting (57.1) and recycling (55.1), as well as awareness (46.9) and sorting and recycling (47.1) in high-income levels. In perceived behavior control, the participants’ results were 47.7 for sorting and 49.6 for recycling in the middle level. Regarding, MI, SI, and GF, the participants’ results in the high-income levels were greater than the others (44.2, 51.1, and 57.1, respectively) toward sorting and recycling. Only awareness between low-income and high-income groups and between the middle-income and high-income groups was significant; therefore, it was supported in some instances and not in others.